Attentional diversion during adaptation affects the velocity as well as the duration of motion after-effects. - Georgiades, M S (2000)
The effects of diverting attention on early motion processing in human vision were studied with a selective adaptation technique. The velocity of motion after-effects (MAEs) produced on a stationary test grating after prolonged exposure to drifting luminance-modulated gratings was measured by matching MAE velocity with that of another physically moving grating. Initial MAE velocities decreased and their rate of decay increased with the distance of the adapting and test gratings from the fixation point. When attention was diverted from the adapting grating, by having subjects process the intermittently changing digit which formed the fixation point, initial MAE velocities were reduced and rate of decay increased, with the largest effect of diversion being found for gratings near the fixation point. The effects of varying attention mimic those of varying adapting duration, rather than adapting contrast or velocity, and appear to reflect a genuine change in motion-processing mechanisms.